Short-term response of metabolic hormones to coronary artery bypass surgery - Nemeth, Adam; Cziraki, Attila; Sulyok, Endre; Horvath, Ivan Gabor; Alotti, Nasri; Rauh, Manfred; Rascher, Wolfgang; Szabados, Sandor (Advances in Medical Sciences, 2014)
To explore the response pattern of plasma adipokine and ghrelin levels to coronary artery bypass graft (CABG) surgery in patients with (on-pump) and without (off-pump) cardiopulmonary bypass (CPB).Sixteen consecutive patients (age: 62 ± 10 years, male: 10) with obstructive coronary artery disease (CAD) who underwent elective CABG surgery with CPB and intraoperative GIK infusion were selected for on-pump group and 19 CAD patients (age: 63 ± 10 years, male: 16) were included in the off-pump group. Blood samples were taken before, during and after surgery. Intraoperative samples were withdrawn simultaneously for peripheral vein and sinus coronarius (SC). Plasma adipokine concentrations were measured by ELISA, those of ghrelin by RIA kits.In response to surgical intervention there was an early, transient fall in plasma levels of adiponectin (p<0.0001) and resistin (p=0.002) followed by an increase to approach their initial values. Plasma ghrelin also increased (p=0.045), this increase, however, was confined to the period of GIK supported CPB. Plasma insulin (p=0.003) and resistin (p=0.009) was significantly higher in the peripheral vein than in SC. The perioperative hormone profile of patients without CPB (off-pump) proved to be comparable to that of on-pump patients in spite of the insulin administration and greater oxidative and inflammatory stress.Adipose tissue-derived factors appear to mediate the metabolic and vascular changes that occur in patients with CABG surgery. Epicardial adipose tissue is unlikely to have major contribution to the development of CAD as adipokines are not elevated in SC independent of the mode of intervention.
EVALuna2:18893